Solubility of Polysaccharides 2017
DOI: 10.5772/intechopen.69864
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Properties of Polysaccharides Solutions

Abstract: Osmotic properties of polysaccharides' solutions and associated biopolymer-solvent and biopolymer-biopolymer type interaction are very important from a technological point of view. The knowledge of osmotic properties of these systems provides the basis to appropriate use of polysaccharides having comply with the relevant technology functions, impart the appropriate texture and forming the sensory properties of the final product. Furthermore, an important issue is the effect of time on the osmotic properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
3
0
1
Order By: Relevance
“…Chitosan is a common natural polymer found in crustacean shells and fungi cell walls which is derived by alkali deacetylation of chitin It is a linear polysaccharide composed of randomly distributed N-acetyl- d -glucosamine (acetylated unit) and β-(1–4)-linked d -glucosamine (deacetylated unit). Chitosan is readily soluble in dilute acidic medium below its pKa (pH = 6.5) while chitin is insoluble in organic and regular solvents [ 45 ]. Chitosan is well known for being relatively cheap with favorable non-toxic, biodegradable, antibacterial, and antifungal properties; as such, it has been used in many medical applications ranging from pharmaceuticals to wound dressings [ [46] , [47] , [48] ], as well as in bioprinting [ 17 , 49 ].…”
Section: Biomaterials and Bioinksmentioning
confidence: 99%
“…Chitosan is a common natural polymer found in crustacean shells and fungi cell walls which is derived by alkali deacetylation of chitin It is a linear polysaccharide composed of randomly distributed N-acetyl- d -glucosamine (acetylated unit) and β-(1–4)-linked d -glucosamine (deacetylated unit). Chitosan is readily soluble in dilute acidic medium below its pKa (pH = 6.5) while chitin is insoluble in organic and regular solvents [ 45 ]. Chitosan is well known for being relatively cheap with favorable non-toxic, biodegradable, antibacterial, and antifungal properties; as such, it has been used in many medical applications ranging from pharmaceuticals to wound dressings [ [46] , [47] , [48] ], as well as in bioprinting [ 17 , 49 ].…”
Section: Biomaterials and Bioinksmentioning
confidence: 99%
“…Salari et al (2017) reported higher concentration of XG in sample showed reduction in taste scores compared to the same concentration of CMC with no undesirable changes on the taste of cream cheese. Moreover, the rigid rodlike structure of XG, as well as its higher hydrophobic property owing to the trisaccharide side chains (glucoronic acid and pyruvic acid groups) makes it less easily disrupted and less miscible with saliva compared to the flexible chains of CMC (Naknean & Meenune, 2010, Joanna et al, 2017. According to Choi et al (2014), the inability of XG filament to be miscible with saliva displayed an uneven thinning effect due to the large size of xanthan's molecules which are about 1 µm in length.…”
Section: S T MC Xg Cmcmentioning
confidence: 99%
“…Among polysaccharides, it is possible to find a broad range of polymers with different charges (cationic, nonionic, anionic, or amphoteric) and conformations (mainly loose rigid helices or randomized coils) [17,18], which offers a broad variety of properties to the formulators, pushing the use of polysaccharide to cover different cosmetic necessities, including rheology modifiers, conditioners, healing and suspending agents, moisturizers, hydrators, and emulsifiers [19,20]. Unfortunately, to date, there is no clear understanding of the true role of polysaccharides in cosmetic products.…”
Section: Introductionmentioning
confidence: 99%